Xpert Bladder Cancer Monitor May Avoid Cystoscopies in Patients Under “Active Surveillance” for Recurrent Bladder Cancer (BIAS Project): Longitudinal Cohort Study - Fasulo, Vittorio; Paciotti, Marco; Lazzeri, Massimo; Contieri, Roberto; Casale, Paolo; Saita, Alberto; Lughezzani, Giovanni; Diana, Pietro; Frego, Nicola; Avolio, Pier Paolo; Colombo, Piergiuseppe; Elefante, Grazia Maria; et al. (Frontiers in Oncology, 2022)
Objectives To test the hypothesis that patients under active surveillance (AS) for Non-muscle Invasive Bladder Cancer (NMIBC) who were negative on longitudinal re-testing by the Xpert® Bladder Cancer Monitor (Xpert BC Monitor) assay may avoid unnecessary cystoscopies and urine cytology (UC). Subjects/patients (or materials) and methods This is a prospective cohort study of patients enrolled in the AS protocol for recurrent NMIBC (Bladder Cancer Italian Active Surveillance, BIAS project), whose urine were analyzed by Xpert BC Monitor upon entry in the study (T0). Patients who had a negative Xpert test and did not fail AS, underwent additional Xpert tests after 4 (T1), 8 (T2), and 12 (T3) months. The clinical utility of Xpert was assessed by determining the number of cystoscopies and UC that could be avoided within 1 year. Results Overall, 139 patients were tested with Xpert at T0. Median follow-up was 23 (IQR 17-27) months. Sixty-eight (48.9%) patients failed AS, 65 (46.7%) are currently on AS and 6 (4.3%) were lost at follow-up. At T0 57 (41.0%) patients had a negative test and 36 (63.2%) are still in AS. In patients with 2 consecutives negative Xpert tests, we could have avoided 73.9% of unnecessary cystoscopies, missing 26.4% failure, up to avoid all cystoscopies with 4 negative tests missing only 12% of failure. All the patients with negative Xpert had negative UC. Failure-free-survival at median follow-up (23 month) stratified for having 0, 1, or ≥2 negative tests was 67.0%, 55.1% and 84.1, respectively. Conclusion Our findings suggest that Xpert BC Monitor assay, when it is longitudinally repeated, could significantly reduce the number of unnecessary cystoscopies and UC during their follow-up.